THE EFFECTIVENESS OF THE STEM APPROACH TO INCREASE STUDENTS' LEARNING OUTCOMES IN LEARNING THE PROPERTIES OF LIQUID OBJECTS - Hamid, Sundari; Sahruddin, Alphian (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
This research aims to determine the effectiveness of the STEM approach on learning outcomes about the properties of liquids in Class VB students at the IKIP I Makassar State Elementary School Complex. This research is a form of research with a quantitative approach, using a type of pre-experimental designs (non-designs) research with a one-group pretest-posttest research design. The design is intended to determine the effectiveness of the STEM learning approach on student learning outcomes in Learning the Properties of Liquids. The average student learning outcomes before implementing the STEM Approach was 76.74, while the average student learning outcomes after implementing the STEM Approach was 86.09. This means that the learning outcomes of students using the STEM approach are better when compared to conventional methods. The difference in learning outcomes is significant, where the Sig. (2-tailed) 0.000 smaller than the sig level. 0.05. This means that the average value of student learning outcomes after implementing the STEM Approach compared to before implementing the STEM Approach is 86.09 > 76.74. The results of the hypothesis test show that the STEM approach is practical in the learning outcomes of class V students at the IKIP I Makassar Complex Public Elementary School. The level of effectiveness of using the STEM approach before and after learning can be seen from the average N-Gain Score of 0.4624 in the interval 0.3 â‰¤ g â‰¤ 0.7 in the medium category. This can be seen from an increase in the average student learning outcomes, initially in the excellent category, to becoming very good categories and the percentage of students who obtained learning outcomes in the good and very good categories, which has increased.